Linguistic features of word problems that cause difficulties for learners across the curriculum: A literature review - Malik, Sara Naseem; Rezat, Sebastian (Proceedings on the Twelfth Congress on the European Society for research in Mathematics Education (CERME 12))

Scaffolding Close Reading of Mathematical Text in Pre-service Primary Teacher Education at the Tertiary Level: Design and Evaluation - Rezat, Sebastian; Malik, Sara Naseem; Leifeld, Markus (International Journal of Science and Mathematics Education)
Abstract Even in the digital age, learning mathematics at an academic level still requires much reading of mathematical text. Research has shown that reading mathematical text requires readers to engage with all the structures of the book and with its pedagogical voice, making connections, and plausible reasoning. Specific practices and strategies that support the close reading of mathematical text have been suggested; however, descriptions and empirical evaluations of materials designed to support these activities are rare. We present the design and first evaluation cycle of materials developed in a design research project that aims to scaffold close reading of mathematical text. The materials were designed and evaluated in a German university course on elementary geometry for first-year teacher education students who study mathematics to become primary teachers. The reading strategies were explained and modeled for students in reading-strategy videos. Additionally, close reading of mathematical text was scaffolded by close-reading tasks and homework tasks and problems that build on the reading strategies and were specifically designed to foster understanding of the mathematical text. Survey data were collected from 296 students to evaluate their use of and attitude toward the different materials. The quantitative results indicate that students used the materials and were generally able to learn the course content by themselves. From all provided materials, they found the close-reading tasks most helpful. A qualitative analysis of answers to open questions revealed issues with different materials, particularly with the script, and requests for additional materials. The issues with the script were categorized inductively. The categories are presented as a qualitative result of the study and discussed.
Keywords: General Mathematics; Education

Prospective teachers’ diagnostic judgments on students’ understanding of conditional probabilities - Dröse, Jennifer; Griese, Birgit; Wessel, Lena (Twelfth Congress of the European Society for Research in Mathematics Education (CERME12))

Entwicklung und Erprobung von professionsorientierten Lernumgebungen zur Wissensvernetzung in der Algebra - Dellori, Anna; Wessel, Lena (Beiträge zum Mathematikunterricht 2022)

Design principles for intertwining local and nonlocal mathematics - The case of relating registers and representations in abstract algebra - Dellori, Anna; Wessel, Lena (Proceedings of INDRUM2022)

Pre-service Teachers' Professional Development: Relating Abstract Algebra and School Algebra - Dellori, Anna; Wessel, Lena (Proceedings of the 24th Annual Conference on Research in Undergraduate Mathematics Education)

Schreiben will gelernt sein: Schreiblerngelegenheiten adaptiv gestalten - Wessel, Lena; Dröse, Jennifer (mathematik lehren)

Exogenous Shocks and Business Process Management - Röglinger, Maximilian; Plattfaut, Ralf; Borghoff, Vincent; Kerpedzhiev, Georgi; Becker, Jörg; Beverungen, Daniel; vom Brocke, Jan; Van Looy, Amy; del-Río-Ortega, Adela; Rinderle-Ma, Stefanie; Rosemann, Michael; Santoro, Flavia Maria; et al. (Business & Information Systems Engineering)
Abstract Business process management (BPM) drives corporate success through effective and efficient processes. In recent decades, knowledge has been accumulated regarding the identification, discovery, analysis, design, implementation, and monitoring of business processes. This includes methods and tools for tackling various kinds of process change such as continuous process improvement, process reengineering, process innovation, and process drift. However, exogenous shocks, which lead to unintentional and radical process change, have been neglected in BPM research although they severely affect an organization’s context, strategy, and business processes. This research note conceptualizes the interplay of exogenous shocks and BPM in terms of the effects that such shocks can have on organizations’ overall process performance over time. On this foundation, related challenges and opportunities for BPM via several rounds of idea generation and consolidation within a diverse team of BPM scholars are identified. The paper discusses findings in light of extant literature from BPM and related disciplines, as well as present avenues for future (BPM) research to invigorate the academic discourse on the topic.
Keywords: Information Systems; Business process management; Exogenous shocks; Challenges; Opportunities

Facilitators’ Orientations Towards Learning Goals, Perceived Challenges, and Teaching Resources for a PD Course on Conditional Probability - Nieszporek, Ralf; Griese, Birgit; Biehler, Rolf (Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference on Teaching Statistics)
The data age has led to curriculum developments promoting the relevance of stochastics in mathematics education. This has resulted in an increased demand for teacher professional development (PD) courses, and thus in a rising number of facilitators for this purpose. Their expertise, however, remains under-researched, even though facilitators are the crucial factor in PD success. Our study aims at revealing how one aspect of facilitator expertise, orientation, is connected to other aspects: views on content goals, perception of possible challenges, and attitude towards teaching resources. The explorations reveal differing orientations and learning goals with identical teaching resources for two facilitators who had also been working as a team for the re-design of the PD course for years.

Revisiting Fundamental Ideas for Statistics Education From the Perspective of Machine Learning and Its Applications - Biehler, Rolf (Bridging the Gap: Empowering and Educating Today’s Learners in Statistics. Proceedings of the Eleventh International Conference on Teaching Statistics)
Fundamental ideas (Burrill & Biehler, 2011) have been specified to structure the curriculum across different age levels and to focus on and revisit the most important ideas. Such ideas must be based on an epistemological analysis of the scientific domain of statistics and its applications. Because these domains are changing, fundamental ideas have to be revisited from time to time. In particular, data science and machine learning have led to new methods and applications in society that must be considered for updating fundamental ideas.

Editorial: Research on Data Science Education - Biehler, Rolf; De Veaux, Richard; Engel, Joachim; Kazak, Sibel; Frischemeier, Daniel (Statistics Education Research Journal)
A very warm welcome to this Special Issue of the Statistics Education Research Journal (SERJ) on data science education. Our hope is to give an overview of selected theoretical thoughts and empirical studies on data science education from a statistics education research perspective. Data science education is rapidly developing but research into data science education is still in its infancy. The current issue presents a snapshot of this developing field.
Keywords: Education; Statistics and Probability

Alles normal?! Daten auf Normalverteilung prüfen–mit schulischen Mitteln - Biehler, Rolf; Langlotz, Hubert; Zappe, Wilfried (mathematik lehren)

Modellieren im Stochastikunterricht: Annahmen hinterfragen, Ergebnisse validieren - Biehler, Rolf; Griese, Birgit (mathematik lehren)

Teaching and Learning Data-Driven Machine Learning with Educationally Designed Jupyter Notebooks - Fleischer, Yannik; Biehler, Rolf; Schulte, Carsten (Statistics Education Research Journal)
This study examines modelling with machine learning. In the context of a yearlong data science course, the study explores how upper secondary students apply machine learning with Jupyter Notebooks and document the modelling process as a computational essay incorporating the different steps of the CRISP-DM cycle. The students’ work is based on a teaching module about decision trees in machine learning and a worked example of such a modelling process. The study outlines the students’ performance in carrying out the machine learning technically and reasoning about bias in the data, different data preparation steps, the application context, and the resulting decision model. Furthermore, the context of the study and the theoretical backgrounds are presented.
Keywords: Education; Statistics and Probability

Facilitators’ views on content goals, learning obstacles, and teaching resources in reference to conditional probability - Griese, Birgit; Nieszporek, Ralf; Biehler, Rolf

Mathematik-Vorkurse zur Vorbereitung auf das Studium – Zielsetzungen und didaktische Konzepte - Lankeit, Elisa; Biehler, Rolf (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)

The role of learning strategies for performance in mathematics courses for engineers - Liebendörfer, Michael; Göller, Robin; Gildehaus, Lara; Kortemeyer, Jörg; Biehler, Rolf; Hochmuth, Reinhard; Ostsieker, Laura; Rode, Jana; Schaper, Niclas (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse

Data Science, Statistics, and Civic Statistics: Education for a Fast Changing World - Ridgway, Jim; Campos, Pedro; Biehler, Rolf (Statistics for Empowerment and Social Engagement)

Mini-Aufgaben in mathematischen Übungsgruppen zur Analysis: Charakteristika von Aufgaben und Abstimmungsverhalten von Studierenden - Bauer, Thomas; Biehler, Rolf; Lankeit, Elisa (Unterstützungsmaßnahmen in mathematikbezogenen Studiengängen - Konzepte, Praxisbeispiele und Untersuchungsergebnisse)